Cyclophosphamide treatment with a comparison in both pediatric rheumatology and pediatric nephrology practices - Gezgin Yildirim, Deniz; Orulluoglu, Emine Yilmaz; Yildiz, Cisem; Acari, Ceyhun; Dundar, Hatice Adiguzel; Akaci, Okan; Bakkaloglu, Sevcan A. (Bmc, 2025)
BackgroundCyclophosphamide (CYC) is an inactive alkylating agent that transforms the alkyl radicals into other molecules and is used in combination with systemic corticosteroids in the treatment of many childhood rheumatic diseases, such as systemic lupus erythematosus (SLE), and ANCA-associated vasculitis (AAV). In recent years, rituximab (RTX), a B-cell-targeting anti-CD20 monoclonal antibody, has emerged as a new alternative treatment modality over CYC for induction therapy of childhood-onset rheumatic diseases. Clinicians adopt different practices for using CYC particularly in relation to indications, posology, pre-treatment laboratory work-up, post-treatment follow-up, and screening pre- and post-treatment vaccination status. This study aimed to evaluate the principles and approaches of administering CYC therapy in pediatric rheumatology and pediatric nephrology practices and to compare the clinician preferences for CYC and RTX in induction therapy of childhood-onset rheumatic diseases.MethodsThis study includes a web-based questionnaire executed on 87 participants (56 pediatric rheumatologists (PRs) and 31 pediatric nephrologists (PNs)). Both pediatric subspecialties evaluated and compared the most common indications for CYC treatment, pre-treatment consent protocols, pre-and post-treatment laboratory tests, dosing strategies, and side effects.ResultsChildhood-onset SLE (95%) and AAV (69%) were the most common diseases for which CYC treatment is used. All clinicians, except 2 PNs prescribed CYC via intravenous route. 61% of the PRs and 71% of PNs reported using a monthly dose of 500 mg/m(2) CYC for 6 months in accordance with the National Institutes of Health (NIH) protocol. All clinicians conducted pre-CYC treatment assessments of complete blood count and kidney function tests. Hepatitis B (82%), chickenpox (76%), and mumps-measles-rubella (72%) were the most frequently assessed vaccines. Adverse effects associated with CYC include cytopenia (86%), nausea (52%), liver toxicity (20%), hair loss (31%), hemorrhagic cystitis (37%), allergic reactions (16%), dyspnea (5%), and infertility (2%). 9 clinicians stated that they performed gonad-sparing interventions before CYC, which clarifies why CYC was more commonly preferred in the induction therapy of SLE and AAV over RTX by both PRs and PNs.ConclusionsClinicians still tend to choose CYC over RTX in induction therapy of SLE and AAV and mostly prefer the high-dose CYC treatment regimen suggested by the NIH.
Keywords: Cyclophosphamide; Pediatric nephrology; Pediatric rheumatology; Rituximab; Side effects; Vaccination